2016
DOI: 10.2147/ijn.s105420
|View full text |Cite
|
Sign up to set email alerts
|

Cabazitaxel-loaded human serum albumin nanoparticles as a therapeutic agent against prostate cancer

Abstract: Cabazitaxel-loaded human serum albumin nanoparticles (Cbz-NPs) were synthesized to overcome vehicle-related toxicity of current clinical formulation of the drug based on Tween-80 (Cbz-Tween). A salting-out method was used for NP synthesis that avoids the use of chlorinated organic solvent and is simpler compared to the methods based on emulsion-solvent evaporation. Cbz-NPs had a narrow particle size distribution, suitable drug loading content (4.9%), and superior blood biocompatibility based on in vitro hemoly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 61 publications
(16 citation statements)
references
References 22 publications
0
14
0
2
Order By: Relevance
“…Results of erythrocyte hemolysis tests showed that when CTX concentration was 5–200 μg/mL, the erythrocyte hemolysis rate of MF-NPs-CTX and FA-PEG-NPs-CTX treatments was still less than 5%, which is in line with the standards. Encapsulation of CTX in the nanoparticles removes the strong hemolysis properties of Tween 80 and improves drug safety[25]. This result confirmed that MF-NPs-CTX and FA-PEG-NPs-CTX had good biosafety levels.…”
Section: Discussionmentioning
confidence: 61%
“…Results of erythrocyte hemolysis tests showed that when CTX concentration was 5–200 μg/mL, the erythrocyte hemolysis rate of MF-NPs-CTX and FA-PEG-NPs-CTX treatments was still less than 5%, which is in line with the standards. Encapsulation of CTX in the nanoparticles removes the strong hemolysis properties of Tween 80 and improves drug safety[25]. This result confirmed that MF-NPs-CTX and FA-PEG-NPs-CTX had good biosafety levels.…”
Section: Discussionmentioning
confidence: 61%
“…TP 5 -NPs were synthesized according to the previously reported method [31]. The detailed process was as follows: First, TP 5 was dissolved in 2.0 mL of anhydrous alcohol, and 1.0 mL of sodium chloride solution with a mass fraction of 12.5% and 1.0 mL of HSA were added into the above solution.…”
Section: Methodsmentioning
confidence: 99%
“…The release of TP 5 from TP 5 -NPs in vitro was determined in phosphate buffer saline (PBS, pH 7.4) containing 20.0% v / v ethanol (the solubility of free TP 5 in the release medium was 88.15 μg/mL) by dialysis method [31,32,33]. The detailed process was as follows: first, TP 5 and TP 5 -NPs were all dissolved or dispersed in 1.0 mL PBS (pH 7.4), respectively.…”
Section: Methodsmentioning
confidence: 99%
“…Apt-NPs-DTX was fabricated using a modified self-assembling method that was described previously. 29 , 30 Briefly, 0.65 mL 15% disodium hydrogen phosphate was injected into 1 mL pure ethanol containing 2 mg DTX with intensive mixing. Next, 0.1 mL PBS containing 19.6 mg BSA and 0.4 mg Apt-BSA monomer was injected into this solution and incubated at 65°C for 10 min.…”
Section: Methodsmentioning
confidence: 99%